PENGELOMPOKAN KELAS TUTUPAN LAHAN DI KABUPATEN JEMBRANA BERDASARKAN EKSTRAKSI CITRA LANDSAT 8 - Aryastana, Putu; Dewi, Listya; Sinda, Longginus; Budha, I Ketut (Fakultas Teknik, Universitas Wiraraja, 2024)
The rapid development of infrastructure as it is today has resulted in the closure of green land or vegetation areas. Jembrana Regency is one of the districts that has experienced a shift in land function due to infrastructure development activities and community needs in land use. This study aims to compare the level of vegetation density and the area of density of vegetation area using the NDVI vegetation index method. The results of land cover classification with Landsat 8 imagery in 2016 and 2022 in Jembrana Regency as a data source to analyze NDVI values using the Supervised Classification method resulted in 5 classes consisting of forests, settlements, vacant land, rice fields, and water bodies. The results of the study explained that there was a decrease in land cover in 2016 and 2022 in forests/vegetation, namely 41.76 km2 or 6.23%, , and water bodies by 0.07 km2 or 5.34% . However, on the other hand, there was an increase in the area of land cover in the class of rice fields, settlements, and vacant land by 21,74 km2 or 38,86%; 14.95 km2 or 50.18%; dan 5,14 km2 or 6,05%.. In addition, the overall accuracy test result of land cover classification is 87.50%. The results showed that the map classified by Landsat 8 imagery could be used.